Answer:
[tex]\frac{2}{y+1}[/tex]
Step-by-step explanation:
Factorise the denominator of the second fraction
y² - 1 = (y - 1)(y + 1) ← difference of squares
To obtain a common denominator
multiply numerator/ denominator of first fraction by (y + 1)
= [tex]\frac{2(y+1)}{(y-1)(y+1)}[/tex] - [tex]\frac{4}{(y-1)(y+1)}[/tex] ← subtract numerators leaving the common denominator
= [tex]\frac{2y+2-4}{(y-1)(y+1)}[/tex]
= [tex]\frac{2y-2}{(y-1)(y+1)}[/tex]
= [tex]\frac{2(y-1)}{(y-1)(y+1)}[/tex] ← cancel common factor (y - 1) on numerator/denominator
= [tex]\frac{2}{y+1}[/tex]